Improving access to information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
workshop CTA and IFLA (International Federation of Library Associations and Institutions) brought together 15 reference librarians, agronomists, trainers and publishers based in anglophone Africa for a workshop from June 15-26, 1987 in Lilongwe, Malawi